Zróżnicowanie morfogenetyczne wsi na obszarze gminy Uniejów - Figlus, Tomasz (Biuletyn Uniejowski, 2014)
This article presents the results of research relating to the morphogenesis of the villages in the community of Uniejów. This work is an attempt to apply retrogressive methods to clarify the process of formation and development of layouts of villages and identify the historical relics of rural forms in contemporary cultural landscape of analyzed area. The study included irregular early medieval villages, regular villages that have passed the regulations associated with the location under the German law in the Middle Ages, the villages from the period of development of the manorial economy, villages from the modern period connected with Dutch settlement, and the villages formed as a result of the process of spatial reorganization in the nineteenth century. Development of rural forms in the community of Uniejów was the result of natural, legal, ownership and socio-agrarian influences. In the early Middle Ages one can identify the irregular layouts in the form of a road villages, an oval and multi-road villages. The process of location under the German law brought the development of settlement forms in the shape of large, regular street and oval villages. In the modern period one can identify the manorial forms as morphological elements closely connected with villages of older origin or the manorial forms as an autonomous settlement units. It is also characteristic that one can recognize many hamlets formed on the basis of division of property. In the late eighteenth and early nineteenth century in the studied area one can identify a couple of row villages inhabited by German population. Significant changes in the settlement network of community of Uniejów took place in the nineteenth century. The processes of regulation and parceling-out implicated the formation of new settlement units in the form of row villages with stripes fields and scattered villages with block layout of the fields.